2012
DOI: 10.1161/circinterventions.111.964874
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Procedural Predictors of Suboptimal Outcome After the Treatment of Drug-Eluting Stent Restenosis in the Unprotected Distal Left Main Stem

Abstract: Background— Few data are available regarding the optimal revascularization strategy for unprotected distal left main coronary artery (UDLM) in-stent restenosis (ISR). Methods and Results— Between April 2002 and December 2008, UDLM-ISR following drug-eluting stent (DES) implantation occurred in 92 of 474 patients (19.4%). Of these, 8 (8.7%) who underwent a coronary artery bypass graft (CABG) were excluded, and the remaining 84 (91.3%) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
4
15
1
Order By: Relevance
“…This is the first study to demonstrate such association between MB‐ISR in UDLM and cardiac mortality. Previous studies have demonstrated that SB‐ISR is more common than MB‐ISR and often patients are asymptomatic . Consistent with the previous reports, which have demonstrated the nonmalignant nature of SB‐ISR, the incidence of cardiac death in SB‐ISR alone was also low in our series (0% at 3‐years).…”
Section: Discussionsupporting
confidence: 91%
“…This is the first study to demonstrate such association between MB‐ISR in UDLM and cardiac mortality. Previous studies have demonstrated that SB‐ISR is more common than MB‐ISR and often patients are asymptomatic . Consistent with the previous reports, which have demonstrated the nonmalignant nature of SB‐ISR, the incidence of cardiac death in SB‐ISR alone was also low in our series (0% at 3‐years).…”
Section: Discussionsupporting
confidence: 91%
“…The occurrence of TLR in our study is higher to that reported in other studies, most probably triggered by high angiographic follow‐up. On the basis of previous reports, TLR is associated with lesion complexity (especially true bifurcation) and the rate of angiographic follow‐up . In our study, the greater lesion complexity of ULMCA when compared to previous studies possibly accounted for the higher observed rate of TLR.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, our group previously reported that SB-ISR had a lesser impact on long-term mortality compared with MB-ISR and that it was a largely asymptomatic and relatively benign phenomenon, especially when the LCx was small. 9 Thus, the higher occurrence of TLR in the 2-SS cases seemed to have a smaller clinical impact than expected.…”
Section: Discussionmentioning
confidence: 78%
“…The characteristics of the ULM lesions, along with details of the PCI procedure, have been described previously. 9,10 A true bifurcation lesion was defined as Medina class 1-1-1, 1-0-1, and 0-1-1. For the original procedure, a 1-SS was defined by the use of a single stent, regardless of lesion type, whereas a 2-SS procedure was defined by the use of 2 stents, regardless of the technique used.…”
Section: Takagi Et Al Comparison Of Stent Strategies In Left Main Dismentioning
confidence: 99%